Pineal-adrenal gland interactions in search of an anti-stressogenic role for melatonin - Van Wyk, Elizabeth Joy (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1993)
The multiple functions of the pineal gland have been collectively interpreted as constituting a general anti-stressogenic role. The adrenal glands play a central role in maintaining homeostasis. The major neuroendocrine consequence of long-term stress is elevated circulating glucocorticoid levels. In this study, the effect of chronic, oral hydrocortisone treatment on pineal biochemistry was investigated in male Wi star rats of the albino strain. The results show that seven days of oral hydrocortisone treatment endows the pineal gland with the ability to increase melatonin synthesis in organ culture. The increase is accompanied by a rise in NAT activity, cyclic AMP levels and enhanced specific binding to the pineal B-adrenergic receptors. It appears that hydrocortisone sensitizes the pineal gland to stimulation by B-adrenergic agonists. thus rendering the pineal more responsive to B-adrenergic agonists. Further studies were directed at demonstrating an anti-stressogenic function for the pineal gland by investigating whether the principal pineal indole, melatonin. could protect against the deleterious effects of elevated. circulating drocortisone levels. The results show that chronic, oral hydrocortisone treatment significantly increases liver tryptophan pyrrolase activity. The catabolism of tryptophan by tryptophan pyrrolase is an important determinant of tryptophan availability to the brain, and therefore, brain serotonin levels. The findings show that melatonin inhibits basal and hydrocortisone-stimulated liver tryptophan pyrrolase apoenzyme activity in a dose-dependent manner. This inhibition suggests that melatonin may protect against excessive loss of tryptophan from circulation and against deficiencies in the cerebral serotinergic system which are associated with mood and behavioural disorders. It was shown that another deleterious effect of chronic hydrocortisone treatment is a significant increase in the number of glutamate receptors in the forebrain of male Wistar rats. The increase in receptor number observed in this study is probably due to an increase in the synthesis of glutamate receptors and is associated with a marked reduction in the affinity of the glutamate receptors for glutamate. possible to demonstrate an receptor number or the For practical reasons, it was not effect of melatonin on either glutamate affinity of glutamate receptors for glutamate in rat forebrain membranes. In view of the neurotoxic effect of glutamate in the eNS, the functional significance of recently described glutamate receptors in the pineal gland was investigated. The results show that 10-4 M glutamate significantly inhibits the isoprenaline-stimulated synthesis of N-acetylserotonin and melatonin in organ culture when the pineal glands were pre-incubated with glutamate for 4 hours prior to stimulation with isoprenalin and when glutamate and isoprenaline were administered together in vitro. GABA, a glutamate metabolite could not mimic the decrease in isoprenalinestimulated melatonin, and it is likely that the observed effects were directly attributed to glutamate. Incubation of the pineal gland with 10-4 M glutamate in organ culture did not affect HIOMT activity in pineal homogenates, but significantly elevated both basal and isoprenaline-stimulated NAT activity. It was concluded that glutamate only inhibits melatonin synthesis in intact pineal glands and not in pineal homogenates. The present study has provided further support for an interaction between the pineal and the adrenal glands. There is an ever increasing likelihood that melatonin is an anti-stressogenic hormone and that the pineal gland may have a protective role to play in the pathology of stress-related diseases.
Keywords: Pineal gland -- Secretions; Melatonin; Adrenal glands; Pineal gland -- Research